A kind of regenerated nylon composite material and preparation method thereof

By combining low-volatility environmentally friendly flame retardant, nanoclay, antioxidant stabilizer and synergist with recovered nylon and using twin-screw extrusion granulation process, a regenerated nylon composite with excellent flame retardant and mechanical properties is prepared by combining low-volatility environmentally friendly flame retardant and nanocils, a double-screw extrusion granulation process is used to prepare a regenerated nylon composite with excellent flame retardant and mechanical Materials solve the problem of insufficient performance of existing recycled nylon materials and broaden their application areas.

CN119144147BActive Publication Date: 2025-02-25SHANGHAI CHUANGDU JUNCHENG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411648882.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25
Estimated Expiration
2044-11-19

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of nylon composite materials, and in particular, relates to a regenerated nylon composite material and a preparation method thereof. The regenerated nylon composite material comprises the following components by weight: 45-65 parts of recycled nylon, 10-20 parts of synergist, 5-10 parts of nanoclay, 3-7 parts of low-volatile environmentally friendly flame retardant and 0.5-2 parts of antioxidant stabilizer. The present invention prepares a regenerated nylon composite material by scientifically combining low-volatile environmentally friendly flame retardant with recycled nylon, synergist, nanoclay and antioxidant stabilizer; the composite material has relatively excellent flame retardant properties and mechanical properties, further expanding the scope of application of regenerated nylon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nylon composite materials, and in particular relates to a regenerated nylon composite material and a preparation method thereof. Background Art

[0002] Nylon, also known as polyamide (PA), is a thermoplastic resin. Nylon 6 and nylon 66 are widely used in automobiles, electronics, machinery manufacturing, textiles and other fields due to their excellent mechanical properties, physical properties, wear resistance, self-lubricating properties, oil resistance, and temperature resistance. However, with the use and aging of these products, a large amount of waste nylon materials are also generated. In order to save resources and protect the environment, it is particularly important to recycle and reuse these waste nylon materials.

[0003] CN110423377A discloses a method for preparing high-purity nylon recycled material, which firstly uses an acidic good solvent to dissolve nylon waste, then adds a weak alkaline precipitating agent, and through the principle of acid-base neutralization, nylon polymer is precipitated from the solution, and high-purity nylon recycled material is obtained after washing and drying. CN114672158A discloses a high-strength composite material based on recycled nylon and its preparation method, which comprises, by weight, 40-50 parts of recycled nylon slices, 30-40 parts of matrix particles, 15-25 parts of polyolefins, 5-10 parts of reinforcing fillers, 5-20 parts of glass fibers and 1-5 parts of additives, and its strength index is similar to that of nylon 66, realizing the reinforcing regeneration of nylon; at the same time, the patent provides a method for regenerating waste nylon material, using trifluoroethanol as a solvent, compounding a small amount of phosphotungstic acid as a depolymerization catalyst, filtering and decolorizing the nylon after slight depolymerization, and then catalyzing polymerization with N-acetyl caprolactam and sodium hydroxide to realize the regeneration of nylon. The above methods have achieved the effective recycling and reuse of waste nylon to a certain extent, but there are still obvious deficiencies in some key properties of recycled nylon materials, such as flame retardancy and mechanical properties.

[0004] During the recycling process of waste nylon materials, their molecular chains may break due to aging, thermal oxidation degradation and other factors, resulting in a decrease in the flame retardant grade of the material and an increase in flammability. At the same time, when subjected to external forces, its mechanical properties such as tensile strength and impact toughness will also be weakened. The degradation of these properties not only limits the application of recycled nylon materials in certain fields with high requirements for safety and structural strength, but also increases the safety risks of the materials during processing and use.

[0005] Therefore, it is necessary to provide a recycled nylon composite material to improve the flame retardant properties and mechanical properties of recycled nylon. Summary of the invention

[0006] In order to overcome the deficiencies of the prior art, one of the purposes of the present invention is to provide a regenerated nylon composite material having relatively excellent flame retardant properties and mechanical properties.

[0007] One of the purposes of the present invention is achieved by the following technical solution:

[0008] A recycled nylon composite material comprises the following components by weight: 45-65 parts of recycled nylon, 10-20 parts of a synergist, 5-10 parts of nanoclay, 3-7 parts of a low-volatile environmentally friendly flame retardant, and 0.5-2 parts of an antioxidant stabilizer; the structural formula of the low-volatile environmentally friendly flame retardant is:

[0009] .

[0010] Furthermore, the preparation process of the low volatility environmentally friendly flame retardant comprises the following steps:

[0011] (1) Lysine, trimethylamine and 4-nitrobenzene phosphorus dichloride were added to chloroform and reacted at 50-60°C for 8-12 hours to obtain intermediate 1;

[0012] (2) Add intermediate 1 and iron powder to acetic acid, react for 16 to 24 hours, and obtain intermediate 2 after treatment;

[0013] (3) Add intermediate 2, triethylamine and diphenylphosphine chloride to chloroform, react at -5-0°C for 1-3 h, at 25-30°C for 2-3 h, and at 60-65°C for 5-7 h, and obtain a low-volatile environmentally friendly flame retardant after treatment.

[0014] Furthermore, the molar ratio of lysine, trimethylamine and 4-nitrobenzene phosphorus dichloride in step (1) is 1: (2-2.5): (1-1.5).

[0015] Furthermore, in step (2), the mass ratio of the intermediate 1, iron powder and acetic acid is 1:(2.1-2.4):(6-7).

[0016] Furthermore, in step (3), the mass ratio of the intermediate 2, triethylamine and diphenylphosphine chloride is 1: (0.9-1.1): (0.7-0.8).

[0017] Furthermore, the antioxidant stabilizer includes one of N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine and triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate.

[0018] Furthermore, the nano clay is montmorillonite; and the synergist is poly-L-lactide-co-caprolactone.

[0019] The second object of the present invention is to provide a method for preparing a regenerated nylon composite material.

[0020] The second object of the present invention is achieved by adopting the following technical solution:

[0021] The method for preparing the above-mentioned recycled nylon composite material comprises the following steps:

[0022] S1: drying and uniformly mixing the recycled nylon, synergist, nanoclay, low volatility environmentally friendly flame retardant and antioxidant stabilizer according to the weight proportions to obtain a mixed material;

[0023] S2: Add the mixture obtained in step S1 into a twin-screw extruder, melt-extrude and granulate to obtain the product.

[0024] Furthermore, in step S1, the drying temperature is 100-120° C., the drying time is 10-12 hours, and the mixing time is 5-10 minutes.

[0025] Furthermore, in step S2, during granulation, the temperature of zone 1 of the twin-screw extruder is 250-260°C, the temperature of zone 2 is 240-250°C, the temperature of zone 3 is 220-240°C, the temperature of zone 4 is 210-230°C, and the screw speed is 200-350r / min.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention prepares a regenerated nylon composite material by scientifically combining a carefully designed low-volatile environmentally friendly flame retardant with recycled nylon, a synergist, nanoclay and an antioxidant stabilizer. The composite material efficiently utilizes waste nylon and exhibits excellent flame retardant and mechanical properties, providing a new strategy for the resource utilization of waste nylon and broadening its application field.

[0028] 2. The low volatility environmentally friendly flame retardant provided by the present invention contains a large number of phosphoric acid amide groups, carboxyl groups and aromatic rings, which realize gas phase and condensed phase flame retardancy through phosphoric acid amide groups, effectively interrupt the combustion process and slow down the decomposition of polymers. Aromatic rings can improve the overall strength, rigidity and thermal stability of polymers, making nylon less likely to deform when subjected to external forces, ensuring that recycled nylon composite materials can maintain good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The figure is a schematic diagram of the preparation process of the low volatility environmentally friendly flame retardant of the present invention. DETAILED DESCRIPTION

[0030] Below, in conjunction with the accompanying drawings and specific embodiments, the present invention is further described. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0031] In order to reduce the impact of impurities on nylon regeneration, the following examples and comparative examples cleaned the recycled nylon waste before preparing the recycled nylon composite materials to remove as much non-nylon materials as possible, and then formed the recycled nylon into granular form through a pelletizer.

[0032] Example 1

[0033] A regenerated nylon composite material comprises the following components by weight: 50 parts of recycled nylon, 15 parts of poly-L-lactide-co-caprolactone, 8 parts of montmorillonite, 5 parts of low-volatility environmentally friendly flame retardant and 1 part of N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

[0034] The preparation process of the low volatility environmentally friendly flame retardant is as follows Figure 1 As shown, the following steps are included:

[0035] (1) Lysine (0.1 mol) and trimethylamine (0.2 mol) were added to 200 mL of chloroform solution, stirred evenly, and heated to 60 °C under nitrogen protection. Then 4-nitrobenzene dichloride (0.1 mol) was added to the above solution in batches. After the addition was completed, the reaction was continued for 8 h, and the solvent was removed by rotary evaporation. The residue was dissolved in 20 mL of DMSO to remove the insoluble trimethylamine hydrochloride, and the solution was added to stirred ethanol (200 mL). After the solid was precipitated, the solid was washed three times with ethanol, and then dried in a vacuum oven at 80 °C to obtain intermediate 1.

[0036] (2) Intermediate 1 (30 g) was added to 200 mL of acetic acid, and then iron powder (65 g) was added. The mixture was stirred at room temperature for 16 h. After the pH was adjusted to 7, unreacted molecules were removed by dialyzing using a dialysis bag (molecular weight cutoff 1000 Da). The solution in the dialysis bag was concentrated and dried to obtain intermediate 2.

[0037] (3) At 0°C, intermediate 2 (39.5 g) and triethylamine (36.5 g) were added to 200 ml of chloroform, and then diphenylphosphine chloride (28.5 g) was added to the reaction system under nitrogen stirring conditions, and the reaction was carried out at 0°C for 3 h. The reaction mixture was then placed at 25°C for 2 h and heated to 62°C for 6 h. Finally, the reaction solution was washed and extracted 6 times with 900 mL of deionized water to remove by-products. The product was obtained from the extract by rotary evaporation and dried in a vacuum drying oven at 80°C for 12 h to obtain a low-volatile environmentally friendly flame retardant.

[0038] The low volatility environmentally friendly flame retardant 1 H NMR (400 MHz, DMSO- d6 ): δ 12.40-12.38 (m, 1H), 8.76-8.73 (m, 1H), 7.80-7.76 (m, 4H), 7.52-7.49 (m, 6H), 7.12-7.08 (m, 2H) , 6.80-6.77 (m, 3H), 3.70-3.65 (m, 1H), 3.40-3.37 (m, 1H), 2.63-2.60 (m, 2H), 1.77-1.25 (m, 6H).

[0039] The preparation method of the regenerated nylon composite material comprises the following steps:

[0040] S1: according to the weight proportion of each component in the formula, the recycled nylon, poly (L-lactide-co-caprolactone), montmorillonite, low volatility environmentally friendly flame retardant and N,N'-bis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine were dried in a drying oven at 100°C for 12 hours, then added into a mixer, stirred for 10 minutes and mixed evenly;

[0041] S2: The mixed material obtained in step S1 is fed into a twin-screw extruder through a feeding port for extrusion granulation. The screw speed is 275 r / min. During granulation, the temperature of zone 1 of the twin-screw extruder is 253° C., the temperature of zone 2 is 243° C., the temperature of zone 3 is 225° C., and the temperature of zone 4 is 215° C.

[0042] Example 2

[0043] A regenerated nylon composite material comprises the following components, measured by weight: 45 parts of recycled nylon, 10 parts of poly-L-lactide-co-caprolactone, 5 parts of montmorillonite, 3 parts of a low-volatile environmentally friendly flame retardant and 0.5 parts of triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate.

[0044] The preparation process of the low volatility environmentally friendly flame retardant comprises the following steps:

[0045] (1) Lysine (0.1 mol) and trimethylamine (0.25 mol) were added to 200 ml of chloroform solution, stirred evenly, and heated to 50 °C under nitrogen protection. Then 4-nitrobenzene dichloride (0.15 mol) was added to the above solution in batches. After the addition was completed, the reaction was continued for 12 hours, and the solvent was removed by rotary evaporation. The residue was dissolved in 20 mL of DMSO to remove the insoluble trimethylamine hydrochloride, and the solution was added to stirred ethanol (200 mL). After the solid was precipitated, the solid was washed three times with ethanol, and then dried in a vacuum oven at 80 °C to obtain intermediate 1.

[0046] (2) Intermediate 1 (30 g) was added to 180 mL of acetic acid, and then iron powder (70 g) was added. The mixture was stirred at room temperature for 20 h. After the pH was adjusted to 7, unreacted molecules were removed by dialyzing using a dialysis bag (molecular weight cutoff 1000 Da). The solution in the dialysis bag was concentrated and dried to obtain intermediate 2.

[0047] (3) At -5°C, intermediate 2 (39.5 g) and triethylamine (40 g) were added to 200 ml of chloroform, and then diphenylphosphine chloride (30 g) was added to the reaction system under nitrogen stirring conditions, and the reaction was carried out at -5°C for 1 hour. The reaction mixture was then placed at 30°C for 3 hours and heated to 65°C for 5 hours. Finally, the reaction solution was washed and extracted 6 times with 900 mL of deionized water to remove by-products. The product was obtained from the extract by rotary evaporation and dried in a vacuum drying oven at 80°C for 12 hours to obtain a low-volatile environmentally friendly flame retardant. This embodiment 1 The H NMR results showed that the structure was consistent with that in Example 1.

[0048] The preparation process of the regenerated nylon composite material comprises the following steps:

[0049] S1: according to the weight proportion of each component in the formula, the recycled nylon, poly (L-lactide-co-caprolactone), montmorillonite, low volatility environmentally friendly flame retardant and triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate were dried in a drying oven at 120° C. for 10 h, added into a mixer, stirred for 5 min and mixed evenly;

[0050] S2: The mixed material obtained in step S1 is fed into a twin-screw extruder through a feeding port for extrusion granulation. The screw speed is 200 r / min. During granulation, the temperature of zone 1 of the twin-screw extruder is 257°C, the temperature of zone 2 is 246°C, the temperature of zone 3 is 230°C, and the temperature of zone 4 is 220°C.

[0051] Example 3

[0052] A regenerated nylon composite material comprises the following components by weight: 65 parts of recycled nylon, 20 parts of poly-L-lactide-co-caprolactone, 10 parts of montmorillonite, 7 parts of low-volatility environmentally friendly flame retardant and 2 parts of N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

[0053] The preparation process of the low volatility environmentally friendly flame retardant comprises the following steps:

[0054] (1) Lysine (0.1 mol) and trimethylamine (0.23 mol) were added to 200 ml of chloroform solution, stirred evenly, and heated to 55 °C under nitrogen protection. Then 4-nitrobenzene dichloride (0.12 mol) was added to the above solution in batches. After the addition was completed, the reaction was continued for 10 h, and the solvent was removed by rotary evaporation. The residue was dissolved in 20 mL of DMSO to remove the insoluble trimethylamine hydrochloride, and the solution was added to stirred ethanol (200 mL). After the solid was precipitated, the solid was washed three times with ethanol, and then dried in a vacuum oven at 80 °C to obtain intermediate 1.

[0055] (2) Intermediate 1 (30 g) was added to 190 mL of acetic acid, and then iron powder (68 g) was added. The mixture was stirred at room temperature for 24 h. After the pH was adjusted to 7, unreacted molecules were removed by dialyzing using a dialysis bag (molecular weight cutoff 1000 Da). The solution in the dialysis bag was concentrated and dried to obtain intermediate 2.

[0056] (3) At -3°C, intermediate 2 (39.5 g) and triethylamine (38 g) were added to 200 ml of chloroform, and then diphenylphosphine chloride (29.2 g) was added to the reaction system under nitrogen stirring conditions, and the reaction was carried out at -3°C for 2 hours. The reaction mixture was then placed at 25°C for 2.5 hours, and heated to 60°C for 7 hours. Finally, the reaction solution was washed and extracted 6 times with 900 mL of deionized water to remove by-products. The product was obtained from the extract by rotary evaporation and dried in a vacuum drying oven at 80°C for 12 hours to obtain a low-volatile environmentally friendly flame retardant. This embodiment 1 The H NMR results showed that the structure was consistent with that in Example 1.

[0057] The preparation process of the regenerated nylon composite material comprises the following steps:

[0058] S1: according to the weight proportion of each component in the formula, the recycled nylon, poly (L-lactide-co-caprolactone), montmorillonite, low volatility environmentally friendly flame retardant and N,N'-bis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine were dried in a drying oven at 110°C for 11 hours, added into a mixer, stirred for 8 minutes and mixed evenly;

[0059] S2: The mixed material obtained in step S1 is fed into a twin-screw extruder through a feeding port for extrusion granulation. The screw speed is 350 r / min. During granulation, the temperature of zone 1 of the twin-screw extruder is 260°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 240°C, and the temperature of zone 4 is 230°C.

[0060] Comparative Example 1

[0061] A recycled nylon composite material, which differs from Example 1 in that: no low-volatile environmentally friendly flame retardant is added.

[0062] Comparative Example 2

[0063] A regenerated nylon composite material, which is different from Example 1 in that montmorillonite is not added.

[0064] Comparative Example 3

[0065] A recycled nylon composite material, which is different from Example 1 in that poly-L-lactide-co-caprolactone is not added.

[0066] Comparative Example 4

[0067] A recycled nylon composite material, which differs from Example 1 in that the low-volatility environmentally friendly flame retardant is replaced by an equal amount of nano aluminum hydroxide (particle size: 10-20 nm).

[0068] Test Example 1

[0069] The performance of the recycled nylon composite materials of Examples 1 to 3 and Comparative Examples 1 to 4 was tested, and the flame retardant grade was tested with reference to UL94, the tensile strength and elongation at break were tested with reference to GB / T1040-2006, the flexural strength was tested with reference to GB / T9341-2000, and the notched impact strength was tested with reference to GB / T1843-2008. The results are shown in Table 1.

[0070] Table 1 Performance characterization of recycled nylon composite materials of Examples 1 to 3 and Comparative Examples 1 to 4

[0071]

[0072] From Table 1, we can see that:

[0073] Compared with Examples 1 to 3, Comparative Example 1 does not add flame retardant, and its flame retardant effect is greatly weakened; Comparative Example 4 replaces the low volatility environmentally friendly flame retardant with an equal amount of nano aluminum hydroxide, and its flame retardant effect is basically unchanged. However, the tensile strength, elongation at break, flexural strength, and notched impact strength of the regenerated nylon composite materials of Comparative Examples 1 and 4 are weaker than those of Examples 1 to 3 to varying degrees; this shows that the low volatility environmentally friendly flame retardant prepared by the present invention can significantly improve the mechanical properties and notched impact strength of the regenerated nylon material while maintaining high-efficiency flame retardancy. This may be because the low volatility environmentally friendly flame retardant prepared by the present invention contains more phosphoric acid amide groups and aromatic rings, and the polyphosphoric acid amide groups can improve the flame retardant properties of the regenerated nylon composite material from two aspects of gas phase flame retardancy and condensed phase flame retardancy, and the aromatic rings can increase the overall strength, rigidity, and stability of the polymer, making nylon less likely to deform when subjected to external forces, thereby improving the tensile strength and flexural strength of the material.

[0074] Compared with Examples 1-3, Comparative Example 2 does not add montmorillonite, and the flame retardant effect is almost the same as that of Examples 1-3; its tensile strength, elongation at break, flexural strength and notched impact strength are all weaker than those of Examples 1-3.

[0075] Compared with Examples 1 to 3, Comparative Example 3 did not add poly-L-lactide-co-caprolactone, and the flame retardant effect was almost the same as that of Example 1; its tensile strength, elongation at break, flexural strength and notched impact strength were all significantly weaker than those of Examples 1 to 3. This indicates that poly-L-lactide-co-caprolactone cooperates with other components to improve the overall performance of the composite material.

[0076] In summary, the regenerated nylon composite materials prepared in Examples 1 to 3 of the present invention have excellent flame retardant properties and mechanical properties.

[0077] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A recycled nylon composite material, characterized in that: The composition comprises the following components by weight: 45-65 parts of recycled nylon, 10-20 parts of synergist, 5-10 parts of nanoclay, 3-7 parts of low volatility environmentally friendly flame retardant and 0.5-2 parts of antioxidant stabilizer; the nanoclay is montmorillonite; the synergist is poly-L-lactide-co-caprolactone; the structural formula of the low volatility environmentally friendly flame retardant is: 。 2. The recycled nylon composite material according to claim 1, characterized in that: The preparation process of the low volatility environmentally friendly flame retardant comprises the following steps: (1) Lysine, trimethylamine and 4-nitrobenzene phosphorus dichloride were added to chloroform and reacted at 50-60°C for 8-12 hours to obtain intermediate 1; (2) Add intermediate 1 and iron powder to acetic acid, react for 16 to 24 hours, and obtain intermediate 2 after treatment; (3) Add intermediate 2, triethylamine and diphenylphosphine chloride to chloroform, react at -5-0°C for 1-3 h, at 25-30°C for 2-3 h, and at 60-65°C for 5-7 h, and obtain a low-volatile environmentally friendly flame retardant after treatment.

3. The regenerated nylon composite material according to claim 2, characterized in that: The molar ratio of lysine, trimethylamine and 4-nitrobenzene phosphorus dichloride in step (1) is 1: (2-2.5): (1-1.5).

4. The recycled nylon composite material according to claim 2, characterized in that: The mass ratio of the intermediate 1, iron powder and acetic acid in step (2) is 1:(2.1-2.4):(6-7).

5. The regenerated nylon composite material according to claim 2, characterized in that: The mass ratio of the intermediate 2, triethylamine and diphenylphosphine chloride in step (3) is 1: (0.9-1.1): (0.7-0.8).

6. The regenerated nylon composite material according to claim 1, characterized in that: The antioxidant stabilizer includes one of N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine and triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate.

7. The method for preparing the regenerated nylon composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: drying and uniformly mixing the recycled nylon, synergist, nanoclay, low volatility environmentally friendly flame retardant and antioxidant stabilizer according to the weight proportions to obtain a mixed material; S2: Add the mixture obtained in step S1 into a twin-screw extruder, melt-extrude and granulate to obtain the product.

8. The method for preparing the regenerated nylon composite material according to claim 7, characterized in that: In step S1, the drying temperature is 100-120°C, the drying time is 10-12 hours, and the mixing time is 5-10 minutes.

9. The method for preparing the regenerated nylon composite material according to claim 8, characterized in that: In step S2, during granulation, the temperature of zone 1 of the twin-screw extruder is 250-260°C, the temperature of zone 2 is 240-250°C, the temperature of zone 3 is 220-240°C, the temperature of zone 4 is 210-230°C, and the screw speed is 200-350r / min.

Citation Information

Patent Citations

  • Preparation method of high-purity nylon regenerated material

    CN110423377A

  • High-strength composite material based on regenerated nylon and preparation method thereof

    CN114672158A

  • Novel flame-retardant nylon heat-conducting material

    CN112251018A

  • Antiviral compounds

    CN115087659A